Understanding students' online learning readiness towards skill-based hospitality courses / Faliza Mahamed Ali ... [et al.] - Mahamed Ali, Faliza; Abdul Karim, Noraida; Samsudin, Azlina; Hamid, Munirah; Mohd Zaki, Mohd Izwan (Universiti Teknologi MARA Cawangan Pulau Pinang, 2022)
The purpose of this study is to evaluate students ' online learning readiness for the skills-based courses in the hospitality higher institution in Terengganu' Malaysia. A 20 items online questionnaire from the five dimensions of the Online Learning Readiness Scale: self-directed learning' computer/internet selfefficacy, motivation for learning, online communication selfefficacy, and learner control was adopted. Five hundred online surveys were distributed, and 482 respondents have been selected as the final sample size. A quantitative research method with convenience sampling and descriptive statistics was adopted to analyze the results using SPSS statistical software. The results revealed that computer and internet self-efficacy are students' highest average mean score, followed by online communication self-efficacy, motivation for learning, self-directed learning, and the lowest average mean score is learner control. Thus, overall scores indicated that students' online readiness for skills-based courses is at a medium level. Based on the statistical results, the study helps educators in hospitality higher learning institutions to engineered appropriate content and delivery methods for skill-based online learning courses. The study concluded by offering suggestions for future research to improve students' readiness towards skill-based online learning courses.